Anesthetic Considerations in a Case of Fahr and Primrose Syndrome - Bhavna Gupta; Lalit Gupta (Research and Practice in Anesthesiology, 2018)
In this review article, brief description, concerns, anesthetic management and perioperative care patients with Fahr syndrome and Primrose syndrome has been made. There is a paucity of literature with respect to management of such cases. There are limited case reports reported in the literature. The literature search has been made by using Google scholar, PubMed, Medline, Medscape and other search-related search engines with the following keywords.